2007
DOI: 10.1086/520118
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Body Size and Sexual Size Dimorphism of a Seed‐Feeding Beetle

Abstract: Body size of many animals varies with latitude: body size is either larger at higher latitudes (Bergmann's rule) or smaller at higher latitudes (converse Bergmann's rule). However, the causes underlying these patterns are poorly understood. Also, studies rarely explore how sexual size dimorphism varies with latitude. Here we investigate geographic variation in body size and sexual size dimorphism of the seed-feeding beetle Stator limbatus, collected from 95 locations along a 38 degrees range in latitude. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
180
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(189 citation statements)
references
References 70 publications
7
180
1
1
Order By: Relevance
“…Environmental gradients are important determinants of resource variation, and in many species, body size varies along gradients of temperature (Ashton and Feldman, 2003;James, 1970), primary productivity (Beaupre, 1995a), and/or seasonality (Ashton, 2001;Boyce, 1979). Additionally, body size in males and females may respond differently to environmental gradients and thus result in geographic variation in sexual size dimorphism (SSD; Dobson and Wigginton, 1996;Stillwell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental gradients are important determinants of resource variation, and in many species, body size varies along gradients of temperature (Ashton and Feldman, 2003;James, 1970), primary productivity (Beaupre, 1995a), and/or seasonality (Ashton, 2001;Boyce, 1979). Additionally, body size in males and females may respond differently to environmental gradients and thus result in geographic variation in sexual size dimorphism (SSD; Dobson and Wigginton, 1996;Stillwell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is often discussed as the primary driver behind large-scale patterns of body size clines (Stillwell et al, 2007). In general, body sizes of endotherms are negatively (i.e., Bergmann's Rule) and ectotherms positively correlated with temperature (Ashton and Feldman, 2003;James, 1970; but see: Olalla-Tárraga et al, 2006), but there is no general agreement on the proximate determinants responsible for these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated SSD of each age group (year) for each population using the SDI index (Lovich and Gibbons 1992), where SDI = [mean size of the larger sex/(mean size of the smaller sex-1)]. This index has the best statistical properties of all dimorphism indexes that have been proposed (Smith 1999;Stillwell et al 2007). We also calculated sex ratios (male:female) of each age group for each population.…”
Section: Discussionmentioning
confidence: 99%
“…The direction and magnitude of SSD varies considerably among the major taxa and among species due to variation in the sources of selection acting in concert to create SSD: variation among taxa/species in the magnitude of sexual selection favouring large size in males (owing to male -male competition or female choice), variation in fecundity selection favouring large size in females (larger females produce more eggs) and variation in a variety of sources of selection favouring small size in both sexes ). In addition, recent studies have shown that the magnitude of SSD, but often not the direction, changes considerably among populations within species (Blanckenhorn et al 2006(Blanckenhorn et al , 2007Stillwell et al 2007a). Although much of this intraspecific variation in SSD is partly genetically based and hence due to selection, some of this variation is also probably due to a sex difference in phenotypic plasticity in body size (Fairbairn 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…Although many environmental and ecological variables induce plasticity in body size and other traits of ectothermic animals (Stillwell et al 2007a;Teder et al 2008;Blanckenhorn 2009), two are particularly important in inducing plasticity in growth and life-history traits: diet quantity/quality and temperature Stillwell et al 2007b). Insects typically mature at larger sizes when raised at lower temperatures and when raised on higher quality diets (Atkinson 1994;Berrigan & Charnov 1994;Stillwell & Fox 2005;Stillwell et al 2007b;Kingsolver & Huey 2008).…”
Section: Introductionmentioning
confidence: 99%